2013
DOI: 10.1055/s-0033-1335637
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and Randomized Study to Evaluate the Clinical Impact of Cap Assisted Colonoscopy (CAC)

Abstract: CAC was without clinical impact on polyp detection rate or performance of colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…In recent years, performance of CAC has increasingly become popular among gastroenterologists. In a prospective and randomized study to evaluate the clinical impact of cap-assisted colonoscopy, Frieling et al [66] found a significant higher cecal intubation time when using a transparent cap. However, there are contradictory results for improving the ADR.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…In recent years, performance of CAC has increasingly become popular among gastroenterologists. In a prospective and randomized study to evaluate the clinical impact of cap-assisted colonoscopy, Frieling et al [66] found a significant higher cecal intubation time when using a transparent cap. However, there are contradictory results for improving the ADR.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…Three studies including 2 prospective RCTs [7,8] and 1 retrospective study [9] , all from Germany describing the EC were included for the review. Six prospective RCTs, 1 each from Germany [10] , Hong Kong [11] , Netherlands [12] , US [13] , South Korea [14] , Australia [15] and 1 retrospective study from Hong Kong [16] describing the CAC were included for the review. One multicenter (Netherlands, Israel and US) RCT describing ERC was also included [17] .…”
Section: Resultsmentioning
confidence: 99%
“…In the prospective studies, the study subjects were grouped into 2 arms based on the type of intervention: EC [7][8][9] or CAC [10][11][12][13][14][15] or ERC [17] versus standard colonoscopy (SC), regular colonoscopy (RC) or conventional colonoscopy (CC). The retrospective studies looked into the EC [9] and CAC [16] performed.…”
Section: Type Of Colonoscopy and Technical Aspectmentioning
confidence: 99%
See 2 more Smart Citations